2017
DOI: 10.1111/ddi.12546
|View full text |Cite
|
Sign up to set email alerts
|

Tertiary remnants and Holocene colonizers: Genetic structure and phylogeography of Scots pine reveal higher genetic diversity in young boreal than in relict Mediterranean populations and a dual colonization of Fennoscandia

Abstract: Aim: Scots pine is one of the dominant tree species in forest ecosystems of the temperate and boreal zones in Eurasia. Since the Tertiary, it has persisted also in the Mediterranean region, forming relict populations. In this study, we investigate rangewide genetic diversity of Scots pine, aiming to provide comprehensive information on the phylogeography and genetic resources of the species.Location: Europe and Asia. Methods: Thirteen paternally inherited chloroplast microsatellite (cpSSR) loci were used to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(52 citation statements)
references
References 82 publications
3
48
1
Order By: Relevance
“…At the same time our work was based on samples obtained from natural populations and was free from such kind of errors. The distribution of the mitochondrial DNA haplotypes based on the nad7 and nad1 markers in the combined data of Naydenov et al (2007), Pyhajarvi et al, (2008), Buchovska et al (2008), Dering et al (2017) and this study is presented in Fig. S1 (Supplemental data).…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…At the same time our work was based on samples obtained from natural populations and was free from such kind of errors. The distribution of the mitochondrial DNA haplotypes based on the nad7 and nad1 markers in the combined data of Naydenov et al (2007), Pyhajarvi et al, (2008), Buchovska et al (2008), Dering et al (2017) and this study is presented in Fig. S1 (Supplemental data).…”
Section: Discussionmentioning
confidence: 83%
“…The analysis was performed at K = 2, 3, 4, 5 and 6. The geographic distribution of the mitochondrial DNA haplotypes identified in our study was manually drawn, and the distribution of mitotypes that is based on the nad7 and nad1 markers from the data of obtained in Naydenov et al (2007), Pyhajarvi et al, (2008), Buchovska et al (2008), Dering et al (2017) and our study was constructed using the program PhyloGeoViz (Tsai, 2010).…”
Section: Variation Of the Coxi Marker Was Determined By A Single Nuclmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of low LMA, thin needles in southern Scandinavian sites may thus be linked to the combination of high moisture availability and relatively moderate temperature conditions resulting from proximity of the warm oceanic current. Alternatively, it might be a result of historical differentiation of populations on opposite shores of the Baltic Sea, perhaps related to the pathways of post‐glacial colonization of Scandinavia (Dering et al., ) or introduction of non‐native genotypes in Southern Sweden. In either case, the similarity of needle cross‐sectional dimensions between southern and northern sites suggests that traits from this group are not crucial components of cold‐climate adaptation in P. sylvestris .…”
Section: Discussionmentioning
confidence: 99%
“…Although it is known that the most important glacial refugia of Scots pine are located on the Iberian Peninsula, the Balkans and Italy (Cheddadi et.al. 2006), it is conceivable that aside from the main refugial area pine could have probably survived in smaller refugia in other parts of Eurasia, including the Pieniny and Tatra Mountains (Wielkie Koryciska and Małe Koryciska) (Staszkiewicz 1993;Ralska-Jasiewiczowa 2004Naydenov et al 2007Pyhäjärvi et al 2008) and also as it is suggested in a recent extensive study of 92 Scots pine population based on mtDNA and cpSSR, there is a possibility of existence cryptic northern refugia, which can explain discordance with the phenomenon of "southern richness and northern purity" observed in this population (Dering et al 2017).…”
mentioning
confidence: 95%